Glass engineering of aminotriazine-based materials with sub-ambient Tg and high kinetic stability. Issue 25 (15th June 2020) - Kara Ali, Zeinab; Iankovitch, Anna; Jokar, Mahboubeh; Maris, Thierry; Lebel, Olivier; Pellerin, Christian
Abstract : Designing molecular glasses with phenyl rings favors a lower T g and higher glass stability compared to cyclohexyl analogues. Abstract : A challenge in glass engineering is the design of molecular glasses combining a high glass kinetic stability (GS) of the amorphous phase with a low (sub-ambient) glass transition temperature ( T g ). Triazine derivatives with arylamino substituents readily form glassy phases that can show outstanding resistance to crystallization. In the present study, a series of 12 analogous compounds incorporating phenylamino and cyclohexylamino groups was synthesized, and their thermal properties and intermolecular interactions were studied. All compounds possess an excellent glass-forming ability, a low T g ranging from 32 °C to as low as −19 °C, and a high GS. While the cyclohexyl derivatives show higher T g, the phenyl derivatives possess a higher GS with some compounds remaining completely amorphous for over three years despite their sub-ambient T g . X-ray diffraction, infrared spectroscopy and DFT calculations reveal that the higher volume occupancy and rotational energy barrier of cyclohexyl groups are the main factors responsible for the compounds' higher T g values but that they also contribute to their higher propensity to crystallize. In counterpart, the planarity of phenyl groups leads to poorer packing and enhances their GS while keeping their T g well below ambient. The formation of hydrogen bonds or competing interactions provides an additional handle to tune the T g of the compounds. Taken together, these studies provide guidelines for the design of molecular glasses with readily tunable thermal properties in view of their functionalization.